Kontribusi Psikoterapi Islam Bagi Korban Penyalahgunaan Narkoba - St. Hajrah Syam; Silfawani Silfawani; Rahmat Hidayatullah (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2023)
Drug abuse is becoming an increasingly serious problem that must be addressed. As a result of drug dependence outside the doctor's prescription, it can damage not only the nervous system, but also physical and psychological disorders in a person. There are several efforts that can be made for the healing process for drug abusers so that they can live their lives normally. One of them is to use a religious approach through Islamic psychotherapy. In Islamic psychotherapy, the treatment and treatment or application of specific techniques on patients who abuse drugs, according to the instructions of the Qur'an and As-Sunnah.The purpose of writing is to find out how Islamic psychotherapy contributes to victims of drug abuse. The research method in this writing uses qualitative methods, so that all references obtained are centered on literature studies such as books, journals, and articles. Based on research on the effects of Islamic psychotherapy on drug addiction patients found by the authors, this study found a positive effect on the mental state of patients in the future and we can pay attention to the risks of drug addiction with this Islamic psychotherapy. technique